Contact-mediated inhibition between oligodendrocyte progenitor cells and motor exit point glia establishes the spinal cord transition zone. - Cody J Smith; Angela D Morris; Taylor G Welsh; Sarah Kucenas (PLoS Biology)
Rapid conduction of action potentials along motor axons requires that oligodendrocytes and Schwann cells myelinate distinct central and peripheral nervous system (CNS and PNS) domains along the same axon. Despite the importance of this arrangement for nervous system function, the mechanisms that establish and maintain this precise glial segregation at the motor exit point (MEP) transition zone are unknown. Using in vivo time-lapse imaging in zebrafish, we observed that prior to myelination, oligodendrocyte progenitor cells (OPCs) extend processes into the periphery via the MEP and immediately upon contact with spinal motor root glia retract back into the spinal cord. Characterization of the peripheral cell responsible for repelling OPC processes revealed that it was a novel, CNS-derived population of glia we propose calling MEP glia. Ablation of MEP glia resulted in the absence of myelinating glia along spinal motor root axons and an immediate breach of the MEP by OPCs. Taken together, our results identify a novel population of CNS-derived peripheral glia located at the MEP that selectively restrict the migration of OPCs into the periphery via contact-mediated inhibition.